Patient outcomes in an antiretroviral programme in the setting of a solo private general practice - Ntshabele, George Molebatsi (My University, 2014)
Background: The HIV/AIDS epidemic is continuing to impact negatively on the health of populations globally. The region most affected by this epidemic is sub-Saharan Africa, with two-thirds of people living with HIV/AIDS located in this region. In order to combat this epidemic, countries are putting up efforts to scale-up the provision of antiretrovirals to affected individuals. South Africa faces challenges similar to other sub-Saharan countries in the scaling-up of antiretrovirals, such as cost of drugs, inadequate laboratory infrastructure and the low and declining number of health professionals. Therefore, the contribution of private general practitioners as part of the overall strategy to combat the HIV/AIDS epidemic needs to be considered. However, the performance of antiretroviral programmes in the private sector are unknown and there is therefore a need to explore patient outcomes in antiretroviral programmes being run by general practitioners in the private sector. The findings of this study will add to understanding what the outcomes of ARV programmes by GPs in private practice could be in a public-private partnership. Aims: The main aim of the study was to evaluate patient outcomes in an antiretroviral programme in the setting of a solo private general practitioner. Methods: This was a cross-sectional study using retrospective data from March 2005 to February 2008. A total of 170 patient records from a private general practitioner’s rooms were examined. The data were analysed using the using the median, interquartile and proportions. The Chi square was used to test for association between baseline characteristics and patient outcomes in the univariate analysis. Results: The increase in median CD4 count was 242 cells/μl and 265 cells/μl at 6 months and 12 months respectively. The proportion of patients who achieved viral suppression at 6 months and 12 months was 75% and 73% respectively. Rate of loss to follow-up was 29% and 38% at 6 months and 12 months respectively, which was much higher than in other settings. Although there were no statistically significant associations established by the study, the patterns emerging from the study showed that the baseline characteristics that were a risk for poor virological outcomes during the period of the study were female gender, younger age group, higher WHO clinical staging, lower CD4 count and higher viral load. Baseline characteristics that were a risk for loss to follow-up during the period of the study were male gender, younger age group, higher WHO clinical staging, lower CD4 count and higher viral load. Conclusion: Patient outcomes in an antiretroviral programme in the setting of a solo private general practitioner are comparable with patient outcomes in antiretroviral programmes in public sector settings in terms of immunological and virological outcomes. However, the lost to follow-up rate was much higher than in public sector settings.
Keywords: Antiretroviral Therapy, Highly Active